Proceedings of the International Conference on Martensitic Transformations: Chicago (The Minerals, Metals & Materials Series,, 2018)
This collection is organized around the central theme of "Martensite by Design." Contributions include design, microstructure, properties, advanced processing and manufacturing, performance, phase transformations, and characterization.